PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. KEDAUNG INDAH CAN Tbk, SURABAYA - Tasya, Pronasagiva; Lisa, Sulistyawati (Jurnal Bisnis Indonesia, 2021)
This study aims to determine: (1) the effect of training and work discipline onemployee performance at PT. Kedaung Indah Can Tbk, Surabaya (2) the effect oftraining on employee performance at PT. Kedaung Indah Can Tbk, Surabaya (3) theeffect of work discipline on employee performance at PT. Kedaung Indah Can Tbk,Surabaya.This research method uses quantitative methods. The population in this study wereemployees of PT. Kedaung Indah Can Tbk, Surabaya. The sampling technique usessaturated sampling, which takes 224 samples. Data analysis and hypothesis testingtechniques used are multiple linear regression analysis, correlation coefficient anddetermination coefficient analysis, F test (simultaneous), t test (partial) which isprocessed using SPSS 20 for windowsBased on the results of multiple linear regression analysis that simultaneously showsthat the independent variables of Training and Work Discipline have a significantinfluence on the dependent variable Employee Performance, as evidenced by theFcount value ≥ F table. Partially shows that the training variable has a significantinfluence on employee performance, as evidenced by the value of t count > t table.The Work Discipline variable partially shows that it has a significant effect onEmployee Performance, as evidenced by the value of t arithmetic > t table. Thevariable that has the most dominant influence on Employee Performance is WorkDiscipline (X2) .Keywords: Training, Work Discipline, Employee Performance  DOI : https://doi.org/10.33005/jbi.v12i1.2608